Optimization of Polymerase Chain Reaction-Based Screening Techniques for the Detection Of Fragile X Syndrome - Alimat, Sharizah (2004)
Fragile X syndrome is the second most common genetic cause of mental retardation. It is caused by a large expansion of a CGG repeat (full mutation) that leads to silencing of the FMRl gene and the absence of the FMRl gene product, a 70 - 80 kDa protein (FMRP). The aim of this study is to establish a rapid and non-radioactive molecular screening technique using PCR and Southern blotting and to qualify as well as quantify the expression level of proteins from the sera of normal and affected individuals using two-dimensional analysis. In order to carry out the investigation, a number of techniques were used in this study including Polymerase chain reaction (PCR), Southern blotting, DNA sequencing and two-dimensional polyacrylamide gel electrophoresis (2D PAGE). In this study, PCR and Southern blotting techniques were optimized and utilized in the amplification of the FMRl gene in the subjects. The results demonstrated that almost all the suspected individuals show the fblly mutated fragments with more than 600 bp and for the premutation stage, higher than 500 bp fragments were amplified. Only a few suspected individuals showed the normal fragment amplification (152 bp to 265 bp). This may be caused by an alternative DNA structure formed from the triplet repeats and also other types of mutation such as point mutation and deletion, or other mentally dysregulation disorder, which block the amplification of the FMRl region. The PCR products were also subjected to DNA sequencing to confirm the sequence data and size. The fragment from normal individual showed the expected sequence (- 130 bp) but the positive individual yielded an unreadable pattern. A template with high GC content template always has the tendency to build secondary structures that block the amplification of the FMRl gene and this might be one of the causes of the incidence. In the 2D PAGE study, the protein expression maps for sera from healthy individuals were compared with maps from patients with suspected fragile X syndrome using PDQuestTM software analysis. PDQuestTM analysis detected 75 % of proteins being conserved between the normal and fragile X serum which most likely are the housekeeping proteins of the samples. Two protein spots of interest (FMRP complex) and another four protein spots (Ig a light chain, Haptoglobin cleaved P chain, IgG y intermediate chain and IgG heavy chain) were found to be 5 fold down-regulated in the serum from a suspected fragile X patient. In addition, there are also two protein spots (albumin proteins) that were over expressed. The results presented here point out that fragile X syndrome may induce changes at the protein level (indirectly rather than directly) that do not occur under all circumstances but nevertheless represent an important feature of this disorder. However, this study relied on measures in the blood, which may not always reflect the situation in other tissues, especially the brain. The expansion sizes or degree of methylation in non-blood tissues could be very different compared to the blood cells. The expression of the FMRP also could be dissimilar between the blood cells and brain cells. Therefore, further studies should be carried out using a larger sample size, which would give better view of the structural, functional and interaction between FMRP protein with other proteins in serum towards gene therapy and drug development purposes.